High-Throughput Analytical Techniques for Determination of Residues of 653 Multiclass Pesticides and Chemical Pollutants in Tea, Part VI: Study of the Degradation of 271 Pesticide Residues in Aged Oolong Tea by Gas Chromatography-Tandem Mass Spectrometry and Its Application in Predicting the Residue Concentrations of Target Pesticides. (27th November 2019) - Chang, Qiao-Ying; Pang, Guo-Fang; Fan, Chun-Lin; Chen, Hui; Wang, Zhi-Bin
Abstract: The degradation rate of 271 pesticide residues in aged Oolong tea at two spray concentrations, named a and b ( a < b ), were monitored for 120 days using GC–tandem MS (GC-MS/MS). To research the degradation trends and establish regression equations, determination days were plotted as horizontal ordinates and the residue concentrations of pesticide were plotted as vertical ordinates. Here, we consider the degradation equations of 271 pesticides over 40 and 120 days, summarize the degradation rates in six aspects (A–F), and discuss the degradation trends of the 271 pesticides in aged Oolong tea in detail. The results indicate that >70% of the determined pesticides coincide with the degradation regularity of trends A, B, and E, i.e., the concentration of pesticide will decrease within 4 months. Next, 20 representative pesticides were selected for further study at higher spray concentrations, named c and d ( d > c > b > a ), in aged Oolong tea over another 90 days. The determination days were plotted on the x -axis, and the differences between each determined result and first-time-determined value of target pesticides were plotted on the y -axis. The logarithmic function was obtained by fitting the 90-day determination results, allowing the degradation value of a target pesticide on a specific day to be calculated. These logarithmic functions at d concentration were applied to predict the residue concentrations of pesticides at c concentration. Results revealed that 70% of the 20 pesticides had the lower deviation ratios of predicted and measured results.